2016
DOI: 10.1080/15384047.2016.1167291
|View full text |Cite
|
Sign up to set email alerts
|

Role of EZH2 histone methyltrasferase in melanoma progression and metastasis

Abstract: There is accumulating evidence that the histone methyltransferase enhancer of zeste homolog 2 (EZH2), the main component of the polycomb-repressive complex 2 (PRC2), is involved in melanoma progression and metastasis. Novel drugs that target and reverse such epigenetic changes may find a way into the management of patients with advanced melanoma. We provide a comprehensive up-to-date review of the role and biology of EZH2 on gene transcription, senescence/apoptosis, melanoma microenvironment, melanocyte stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 153 publications
(257 reference statements)
1
34
0
Order By: Relevance
“…Gene ACSL5 has been observed to be critical to the expression of tumor‐related factor MCAM, indicating its potential effect on melanoma . Gene EZH2 has been shown to contribute to the transcriptional silencing of tumor suppressor and differentiation genes and be involved in melanoma progression and metastasis . The expression of gene ATP5A1 has been detected prevalently in the cytoplasm of melanoma cells .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene ACSL5 has been observed to be critical to the expression of tumor‐related factor MCAM, indicating its potential effect on melanoma . Gene EZH2 has been shown to contribute to the transcriptional silencing of tumor suppressor and differentiation genes and be involved in melanoma progression and metastasis . The expression of gene ATP5A1 has been detected prevalently in the cytoplasm of melanoma cells .…”
Section: Resultsmentioning
confidence: 99%
“…43 Gene EZH2 has been shown to contribute to the transcriptional silencing of tumor suppressor and differentiation genes and be involved in melanoma progression and metastasis. 44 The expression of gene ATP5A1 has been detected prevalently in the cytoplasm of melanoma cells. 45 The MSH6 expression has been observed to be absent or extremely low in benign nevi and increased in a subset of primary melanoma samples and suggested as a valuable marker to improve prognosis assessment in primary melanoma.…”
Section: Skcm Datamentioning
confidence: 99%
“…Therefore, EZH2 is currently considered a promising drug target, and multiple inhibitors of EZH2 have been developed, some of which are in clinical trials [ 21 ]. Moreover, recent studies have shown that EZH2 also plays a critical role in the proliferation and survival of melanoma [ 19 , 22 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma cells harbor the Y641 activating mutation within the catalytic SET domain that was first described in Diffuse large B-cell (DLBC) lymphoma. Numerous studies have identified an association between aberrant EZH2 expression and melanoma progression [38]. Although EZH2 SNVs have not been comprehensively investigated in this setting, further translational studies are warranted.…”
Section: Resultsmentioning
confidence: 99%